Kefektifan LKS Berbasis STEM (Science, Technology, Engineering and Mathematic) untuk Melatih Keterampilan Berpikir Kritis Siswa pada Pembelajaran Fisika SMA (UPEJ Unnes Physics Education Journal, 2019)
The thinking skills taught in schools are very varied and useful for training students to be ready to dive in society. The Student Worksheet based on STEM is expected to be used as a medium to train students' critical thinking skills. The primary purpose of this research is to analyze the effectiveness of Student Worksheets Based on STEM as a tool to train students' critical thinking skills in physics learning at senior high school. Therefore, this research is focused on identifying (1) effectiveness of Student Worksheets Based on STEM as a learning tools; (2) profile of critical thinking skills of students after STEM-based LKS-based learning. This research uses a quasi-experimental method in One Group Pretest-Posttest Design form. The subjects of this research were grade XI students at SMA 1 Subah, while the object of the research was the Effectiveness of student worksheets based on STEM to Train Critical Thinking Skills. The instrument in this research is a matter of critical thinking skills with the method of data collection in the form of Pretest-Posttest. Then that data is analyzed by descriptive statistics and inferencing statistics. The conclusion of this research is the n-gain of worksheets based on STEM as a learning tool reaches 0.55 so that its effectiveness is categorized in the medium. The profile of critical thinking skills of students has increased after the STEM-based LKS-assisted learning.